Implementing Dynamic Mathematics Resources with GeoGebra at the College Level - Dikovic, Ljubica (International Journal of Emerging Technologies in Learning (iJET), 2009)
The dynamic nature of linear and vector algebra, differential calculus or integration, could be in a conjunction with dynamic/interactive method of display. Although GeoGebra provides multiple representations of mathematical objects, it can help students to discover connections between mathematical objects and their graphical representation. Students take more responsibility for their own learning, and the dynamics of classroom activity shift to more discussion, interest, motivation to study and cooperative learning. The contribution of this paper is that new trends in technology and learning are shown. In technical sense, this paper presents Geogebra applet, which could be especially important for the future development of e-learning of College mathematics. In methodological sense, contribution of this paper is presentation of methodological frames on several specifics examples. The aim of this paper to show how concepts of dynamic geometry can be applied for topics in calculus with suggested GeoGebra software tools. In addition, author emphasizes the important role of free open-source software packages for mathematics teaching world-wide.